IMPROVE STUDENTS' MATHEMATICAL CRITICAL THINKING SKILLS SUMATERA UTARA ISLAM: USING MODELS FOR PROBLEM-BASED LEARNING - Syahlan Syahlan; Rianita Simamora (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
This study's objective was to determine the effects of the problem-based learning model on students enrolled in the mathematics education program at the Islamic University of North Sumatra while they studied to improve their critical thinking skills. This type of quasi-experimental study aims to determine how the participant's parameters are affected by the treatment.